Cover: International Journal of Intelligent Systems, Volume 37 Issue 6 June 2022. Issue 6 (27th April 2022) - Joo, Chonghyo; Park, Hyundo; Lim, Jongkoo; Cho, Hyungtae; Kim, Junghwan
Abstract : Cover Caption : The cover image is based on the Research Article Development of physical property prediction models for polypropylene composites with optimizing random forest hyperparameters by Chonghyo Joo et al., https://doi.org/10.1002/int.22700 .